Saturation association between serum 25-hydroxyvitamin D levels and mortality in elderly people with hyperlipidemia: a population-based study from the NHANES (2001-2016) - Pan, Guang-hui; Zhang, Jun-qing; Sun, Yi-yan; Shi, Yue-hui; Zhang, Fa-rong (Frontiers in Endocrinology, 2024)
Background: 25-hydroxyvitamin D is the body's main storage form of vitamin D and is internationally recognized as the best indicator of vitamin D status in the human body. There is a scarcity of research investigating the interrelationship between serum 25-hydroxyvitamin D (25(OH)D) levels and mortality among elderly individuals with hyperlipidemia. To address this knowledge gap, we examined the association between serum 25(OH)D levels and mortality in an older hyperlipidemic population from NHANES, while controlling for other influential factors. The study sought to elucidate the correlation between serum 25(OH)D levels and mortality about all-cause mortality, cardiovascular disease (CVD), malignant neoplasms, and mortality from other causes. Methods: The data from NHANES 2001-2016, including 9,271 participants were analyzed to examine the association between serum 25(OH)D levels and mortality. The interrelationship was illustrated using Kaplan-Meier curves and restricted cubic splines, while the Cox proportional hazards model was utilized to estimate the multifactor adjusted hazard ratio (HR).Results: This study included 9,271 participants (43.28% male) with an average age of 69.58 years, and the average duration of participant follow-up was 88.37 months.Kaplan-Meier curves demonstrated that lower serum 25(OH)D levels were associated with increased risks of all-cause mortality, cardiovascular mortality, malignant neoplasm mortality, and mortality from other causes. This negative association was further confirmed by the Cox proportional hazards models. Additionally, restricted cubic splines not only revealed this negative association but also highlighted the saturated serum 25(OH)D levels. Moreover, subgroup analyses indicated that the inverse correlation between serum 25(OH)D levels and all-cause mortality was more pronounced in the non-obese and smoking population. And the inverse correlation with mortality from other causes was even stronger in the non-obese population.In the elderly population with hyperlipidemia, 25(OH)D serum levels were negatively correlated with both cause-specific mortality and all-cause mortality.Moreover, there was a threshold effect in this negative association.